Active screening and molecular epidemiological characteristics of fecal colonization by carbapenem-resistant Enterobacterales in intensive care unit wards of a tertiary hospital in Shanghai, China - Zhang, Hui; Zhou, Cong; Xu, Maosuo; Shen, Chunmei; Shen, Fang; Lin, Yong (Frontiers in Public Health, 2025)
BackgroundActive screening for fecal colonization by carbapenem-resistant Enterobacterales (CRE-FC) and interventions in intensive care unit (ICU) wards have become important measures to prevent carbapenem-resistant Enterobacterales (CRE) infection. However, limited data are available on the molecular epidemiology and homology analysis of CRE-FC. This study tried to investigate the molecular epidemiology characteristics and homology of CRE-FC in ICU wards to provide evidence for CRE transmission.MethodsFrom March 1, 2022 to February 28, 2023, fecal swabs from 435 ICU patients were analyzed using resistant bacteria chromogenic plates. Duplicate strains from the same patient were excluded. Infection prevention and control (IPC) measures were implemented for patients with positive CRE screening results. Bacterial identification, antimicrobial susceptibility testing, multilocus sequence typing (MLST), capsule serotypes, whole-genome sequencing (WGS), and core-genome MLST (cgMLST) were conducted to analyze the molecular epidemiological features and homology of these strains.ResultsThe prevalence of CRE-FC in ICU wards was 12.6% (55/435). The predominant CRE-FC was Klebsiella pneumoniae (83.6%, 46/55) and Escherichia coli (9.1%, 5/55). Active screening and IPC interventions in 2022 reduced the CRE infection rate decreased from 11.4 to 7.1%. MLST analysis of 46 carbapenem-resistant K. pneumoniae (CRKP-FC) strains showed that ST11 was the dominant sequence type (71.7%, 33/46), followed by ST15 (26.1%, 12/46) and ST290 (2.2%, 1/46). All ST11 and ST15 strains carried blaKPC-2, 10 of the ST15 strains additionally carried both blaKPC-2 and blaOXA-1. Phylogenetic analysis revealed two major clades: ST11 and ST15.ConclusionCRKP-FC was predominant in CRE-FC. Furthermore, phylogenetic analysis suggested that CRKP-FC had clonal spread in ICU wards, with ST11-KL64 as the main clone. Active CRE-FC screening and IPC interventions can effectively reduced CRE infection rates.